Hubungan antara body image dan body dysmorphic disorder pada member fitness center - Wenur, Claudeo Primus; Kalesaran, Angela Fitriani Clementine; Asrifuddin, Afnal (Holistik Jurnal Kesehatan, 2025)
Background: Body Dysmorphic Disorder (BDD) is a mental disorder characterized by an excessive obsession with physical defects that often go unnoticed by others. The prevalence of BDD varies between 0.5 and 3.2% and can affect individuals aged 5 to 80 years, with a slightly higher prevalence in women. BDD often emerges in adolescence and significantly impacts daily life, particularly among gym members. Research suggests that factors such as a history of abuse and stigma contribute to BDD. Purpose: To explore the relationship between body image and body dysmorphic disorder among gym members. Method: This was an observational analytical study with a cross-sectional design. A sample of 96 respondents was selected using simple random sampling. The research instruments used the MDDI questionnaire to assess BDD and the MBSRQ-AS to assess body image. Univariate analysis was conducted to describe the characteristics of the respondents and each variable. Bivariate analysis was performed using the chi-square test. Results: The bivariate analysis using the chi-square test between the independent variable of body image and the dependent variable of BDD yielded a p-value <0.05. Conclusion: There is a significant relationship between body image and body dysmorphic disorder in fitness center members.   Keywords: Body Dysmorphic Disorder; Body Image; Fitness Center; Members.   Pendahuluan: Body Dysmorphic Disorder (BDD) adalah gangguan mental yang ditandai oleh obsesi berlebihan terhadap cacat fisik yang sering tidak diperhatikan orang lain. Prevalensi BDD bervariasi antara 0.5-3.2% dan dapat memengaruhi individu dari usia 5-80 tahun dengan kecenderungan sedikit lebih tinggi pada perempuan. BDD sering muncul pada masa remaja dan berdampak signifikan pada kehidupan sehari-hari, terutama di kalangan anggota fitness center. Penelitian menunjukkan bahwa factor, seperti riwayat penyalahgunaan dan stigma berkontribusi terhadap BDD. Tujuan: Untuk mengeksplorasi hubungan antara body image dan body dysmorphic disorder pada member fitness center. Metode: Penelitian observasional analitik dengan desain potong lintang. Jumlah sampel sebanyak 96 responden yang dipilih secara simple random sampling. Instrumen penelitian menggunakan kuesioner MDDI untuk menilai adanya BDD dan MBSRQ-AS untuk menilai body image. Analisis univariat dilakukan untuk mendeskripsikan karakteristik responden dan setiap variabel. Sementara analisis bivariat dilakukan dengan uji chi-square. Hasil: Analisis bivariat menggunakan uji chi square antara variabel bebas body image dan variabel terikat BDD didapatkan nilai p < 0.05. Simpulan: Terdapat hubungan yang signfikan antara body image dengan body dysmorphic disorder pada member fitness center.   Kata Kunci: Body Dysmorphic Disorder; Body Image; Fitness Center; Member.